Inclusion of marbofloxacin in PMMA orthopaedic cement - Cariou, M.; Boulouis, H. J.; Moissonnier, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
This in vitro experimental study investigated the feasibility for marbofloxacin, a veterinary fluoroquinolone antibiotic, to retain its antibacterial activity after its inclusion in polymethylmethacrylate (PMMA) cement. The assays were conducted on gelose cultures of various types of bacteria isolated from canine spontaneous osteomyelitis. The efficiency of the antibiotics was assessed by using an antibiogram method. Resistance of marbofloxacin to the temperature observed during PMMA polymerization, antimicrobial effect of galenic, useful concentrations and comparison with gentamicin (reference antibiotic for this use) were evaluated. Marbofloxacin retained its antimicrobial activity after being heated to high temperatures reached during polymerization. The more effective galenic form to incorporate into the PMMA monomer was the marbofloxacin powder and the appropriate concentration was 1/40°. In this experiment, marbofloxacin included in PMMA showed a good antimicrobial activity; however this activity was lower than gentamicin added to PMMA on Gram + and Pseudomonas bacteria.Therefore, it seems useful to incorporate marbofloxacin to PMMA cement to treat, or to prevent, osteomyelitis associated with marbofloxacin sensitive bacteria.Nevertheless, the development of a marbofloxacin-PMMA cement requires further evaluation, especially pharmacological, biomechanical and clinical.
Keywords: Polymethylmethacrylate; marbofloxacin; osteomyelitis; orthopaedic cement